Evaluation of an Enzyme Immunoassay for the Detection of Methadone Metabolite EDDP [2‐Ethylidene‐1, 5‐Dimethyl‐3, 3‐Diphenylpyrrolidine] in Urine. Issue 2 (6th January 2014) - Wolf, Carl E.; Goldstein, Ashley; Poklis, Justin L.; Poklis, Alphonse
<x xml:space="preserve">Abstract</x> Background We evaluated a new EDDP [2‐ethylidene‐1, 5‐dimethyl‐3, 3‐diphenylpyrrolidine] enzyme immunoassay (EDDPI; Lin‐Zhi International, Inc., Sunnyvale, CA) for the detection of this primary methadone urinary metabolite. Methods All specimens were tested with two different cutoff calibrators at 150 and 300 ng/ml EDDP on an ADVIA 1200 Chemistry System auto‐analyzer. Controls containing 0, −25% (negative control), and +25% (positive control) of the cutoff calibrators (Lin‐Zhi) were analyzed with each batch. All urine specimens were then analyzed by high‐pressure liquid chromatography/ mass spectrometry/mass spectrometry (HPLC‐MS/MS) for EDDP. Results Approximately, 42% (151) of the 362 specimens yielded positive results by the EDDP assay at 150 and/or 300 ng/ml cutoff values. Of these specimens, HPLC‐MS/MS confirmed the presence of EDDP > 25 ng/ml in all 151 specimens. No specimen yielding negative EDDPI results contained EDDP by HPLC/MS/MS. At 150 ng/ml cutoff, the EDDPI demonstrated a sensitivity of 1.00, a specificity of 0.986, and an overall agreement of HPLC/MS/MS of >99%. At 300 ng/ml cutoff, the EDDPI demonstrated a sensitivity of 1.00, a specificity of 0.959, and an overall agreement of HPLC/MS/MS results of 97.5%. Conclusion The Lin‐Zhi EDDPI provides a precise, reliable method for the routine detection of methadone metabolite in urine specimens, particularly in pain management compliance testing.